Supplemental one‐carbon metabolism related B vitamins and lung cancer risk in the Women's Health Initiative. Issue 5 (25th February 2020) - Brasky, Theodore M.; Ray, Roberta M.; Navarro, Sandi L.; Schenk, Jeannette M.; Newton, Alison M.; Neuhouser, Marian L.
Abstract : We and others have reported associations between B vitamins principally involved in one‐carbon metabolism and increased lung cancer risk; however, results for women have been inconsistent. Here we report on the association of supplemental vitamins B6, folic acid and B12 intake and lung cancer risk using data from the Women's Health Initiative (WHI) study of postmenopausal women. Between 1993 and 1998, 161, 808 women were recruited to participate in the WHI at 40 clinical centers in the US. After exclusions, 159, 232 women were available for analysis and followed prospectively for an average of 18.3 years. Among them, 3, 836 incident lung cancer cases were diagnosed. At baseline, supplemental B vitamins from multivitamins, vitamin mixtures and individual supplements were assessed. Adjusted Cox regression models were used to estimate hazard ratios (HR) and 95% confidence intervals (CI) for associations between supplemental B vitamin intake and lung cancer risk. Relative to no intake, women who took ≥50 mg/day of vitamin B6 had 16% (HR 0.84, 95% CI: 0.71–0.99) reduced lung cancer risk. Associations did not differ significantly by smoking status or lung cancer histology. Intakes of folic acid and vitamin B12 were not associated with risk. There is a need for replication of our findings from other large, prospective studies with similar high‐quality measurement of supplement intakes before any recommendations can be made at present on B6 supplementation for lung cancer prevention in women. Abstract : What's new? Although the association between dietary intakes of B vitamins and lung cancer risk has been investigated, very few studies have examined the role of B vitamins from supplemental sources, especially in women. Based on data from the Women's Health Initiative prospective cohort of postmenopausal women, this study is thus far the largest and best powered to examine associations of B vitamins intake from dietary supplements with lung cancer risk in women. Although the findings suggest a 16% reduced lung cancer risk associated with ≥50 mg/d of vitamin B6 (over 30 times the Recommended Dietary Allowance), this work requires replication.